The influence of internally architected voids in the creation of high-strength, low-weight 3D-printed cobalt-chromium prototypes - Abdullah Jasim Mohammed; Ahmed Asim Al-Ali (Wolters Kluwer Medknow Publications, 2024)
Background: The additive manufacturing technology made the topology optimization technique feasible. This technique can indefinitely reduce the weight of the printed items with a promising increase in the mechanical properties of that item. Materials and Methods: In the current experimental study, 50 samples were fabricated for a 3-point bending test. They were divided into (n = 5) as a control Group 1 free of internal geometries, (n = 15) for each of Groups 2-4, and they were subdivided into (n = 5) for each percentage of reduction per volume (10%, 15%, and 20%). Spherical, ovoid, and diamond shapes were each group's fundamental geometries, respectively. Cylindrical tunnels connected the voids in each group. Radiographic images were performed to validate the created geometries, the weight was measured, and flexural strength and modulus of elasticity were calculated. Data were analyzed by one-way ANOVA and Duncan's post hoc tests at P < 0.05. Results: The weight results showed a significant reduction in mass. The flexural strength of Group 2 at a 10% reduction per volume had the highest mean significantly without compromising the elastic modulus. In comparison, the means of group 4 at 20% reduction showed the lowest level of toughness. Conclusion: The weight was reduced according to the reduction percentage. The flexural strength of Group 2 at a 10% reduction showed the highest degree of toughness among all groups. The void shape and density influenced the mechanical properties tested.